X-efficiency and Loan Loss Provision Decisions of Hong Kong Banking System - Wang, Jing (2013)
This thesis estimates the X-efficiency (both cost efficiency and profit efficiency) of banks in Hong Kong during the period from 2005 to 2012 and the possible determinants of X-efficiency. It also analyses the loan loss provision decision Hong Kong banking system. Based on a Battese and Coelli (1995) model under stochastic frontier approach, this thesis finds that Hong Kong banks are more cost efficient than profit efficiency and both efficiency scores do not change in tandem. With regard to the loan loss provision study, generalised-method-of-moment technique is utilised to establish a dynamic model. The results show that loan loss provision management of Hong Kong banks does not follow any prior hypothesis (i.e. procyclicality, capital management and income smoothing). The shining point of this thesis is both the empirical model is created from risk management perspective. Specifically, the X-efficiency model includes capital level as risk control factor; the loan loss provision model involves profit efficiency and the lagged value of profit efficiency to examine the provision behaviour from business perspective.